Effectiveness analysis of deceleration capacity and traditional heart rate variability in diagnosing vasovagal syncope - Guo, Yongzhe; Lin, Tao; Lin, Nanyu; Lin, Huizhong (Frontiers in Cardiovascular Medicine, 2024)
Background: Vasovagal syncope (VVS) is a common clinical condition that lacks effective medical detection methods. Aim: To explore an objective clinical indicator in diagnosing VVS. Methods: The clinical data of 243 syncope patients from June 1, 2015 to July 31, 2023 were retrospectively analyzed, including 108 patients with tilt test (TTT) result negative and the other 135 TTT (+) patients. The association between VVS and various heart rate variability (HRV) indicators was analyzed by relevant statistical methods.Results: A total of 354 patients considered for VVS were screened, leaving 243 samples. The variables with a statistical significance between the TTT (-) group and the TTT (+) were: sex, age, deceleration capacity (DC), standard deviation of all normal-to-normal intervals (SDNN). Multivariate logistic regression revealed DC (OR: 1.710, 95%CI: 1.388-2.106, P<0.001) and SDNN (OR: 1.033, 95%CI:1.018-1.049, P<0.001) as independent risk factors. ROC analysis showed a significant difference for both DC and SDNN in between-group comparisons [the corresponding areas under the curve: 0.789 (95% CI: 0.730-0.848) and 0.702 (95% CI: 0.637-0.767); the cut-off value: 7.15 and 131.42; P<0.001, respectively].DC can serve as an objective and accessible clinical indicator to distinguish VVS, in which a numerical value higher than 7.15 ms may indicate an increasing syncope risk.